Nutritional concepts of health promotion in sub urban community: focus on obesity and hypertension - Peter, Malachy B.; Nwose, Ezekiel U.; Ofili, Charles; Peters, Esegbue (International Journal Of Community Medicine And Public Health, 2023)
Many obese and hypertensive individuals reside in suburban areas with poor health infrastructure and low levels of public awareness. The adult morbidity and mortality rates are currently being dominated by diet-related non-communicable diseases like obesity, hypertension, and metabolic syndrome in various countries. Applying both individualized and community-based health promotion strategies can result in the prevention and control of obesity and hypertension. This study examined the role of nutrition in promoting good health, preventing and treating obesity and hypertension in suburban areas. The prevalence of diet-related non-communicable diseases has been notably reduced as a result of health promotion programs. A diet high in dietary fiber, rich in fruits, vegetables, whole grains, lean meats, fish, legumes, non-tropical vegetable oils, and nuts (in moderation) has been promoted. This needs to be adjusted to take into consideration the required calorie intake, unique dietary preferences based on culture and individual, as well as nutrition therapy for various medical conditions.